Development of Problem-Based Integrated Student Worksheets (LKPD) in Thermochemistry Class XI High School - Angelina Barus, Maria; Purba, Jamalum (Riviera Publishing, 2025)
This study aims to develop a Problem-Based Learning (PBL) student worksheet (LKPD) integrated with scientific literacy on the topic of thermochemistry for Grade XI senior high school students, and to evaluate its feasibility and student responses. The research employed a Research and Development (R&D) method using the 4D development model (Define, Design, Develop, Disseminate), limited to the development stage. The development process began with needs analysis, material and layout design, product development, and expert validation. The instruments used included a BSNP-based feasibility assessment sheet and a student response questionnaire. Validation results from three lecturers and two chemistry teachers indicated that the developed LKPD is valid and highly feasible, with an average feasibility score of 3.62. Meanwhile, product testing conducted on Grade XI MIPA students showed very positive responses with an average score of 3.65. These findings indicate that the PBL-based LKPD integrated with scientific literacy is effective in improving students' understanding of thermochemistry concepts, motivating them, and enhancing critical thinking skills and scientific literacy in chemistry learning. This LKPD also has the potential to serve as an innovative teaching material aligned with the Merdeka Curriculum.